Review of the Elemental Status in Blood Serum in Patients with Ischemic Stroke - Anatoliy V. Skalny; Anatoliy D. Fesyun; Maxim Yu. Yakovlev; Sergey A. Savko; Evegeniya D. Namiot (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2022)
The study of the elemental status in the modern paradigm of medical diagnostics occupies an increasingly large niche due to the possible use of trace elements as possible predictors of cerebrovascular pathologies. Moreover, the great importance of the elemental component in the main enzymatic systems of metabolism allows us to consider them also as a therapeutic target. There are many mechanisms in the pathophysiology of stroke development, each of which, in one way or another, is mediated through the interaction of regulatory proteins with trace elements as cofactors. Therefore, it is necessary to pay close attention to elemental homeostasis in the focus of ischemic pathologies. Aim. Systematization of the known pathogenetic effects of the most metabolic homeostasis important elements on the course of stroke, both contributing factors to earlier rehabilitation and minimal neurological deficit after the ischemic event itself, and factors aggravating the recovery process and leading to serious neurological consequences. This pursues not only a prognostic goal to determine the severity of ischemia or to identify risk groups with certain shifts in elemental constants, but also the therapeutic one - to replace the falling functions of the dropping metabolic agents, as happens with the elements involved in antioxidant systems. It is also necessary to develop a methodology for stopping the excess of nerve cells mediating excitotoxicity with calcium ions, which closes the vicious circle of vascular necrosis with additional destruction of the nervous tissue. Conclusion. The conclusions that we can summarize quite convincingly indicate a significant contribution of the elemental status to the pathogenesis of ischemic stroke. Dysregulation of the elemental component can force the damaging effect of ischemia on brain cells. At the same time, many elements show a surplus during an ischemic event: Li, I, Mn, Zn, As, Se, Pb, Sr, Ni, however, not all of the presented elements negatively affect the course of stroke, since an increase in the level of some metals may be compensatory in nature, and for their further applicability as diagnostic and therapeutic agents, similar analytics are required.